OPTIMALISASI AUTOMATIC CHANGE OVER (ACO) UNTUK PELANGGAN PREMIUM PT PLN UP3 BULUNGAN - Ujang Wiharja; Abdul Kodir (TEKNOKRIS, 2023)
Electrical energy a very dominant in people's daily lives, so that if a power outage will result in losses. In order to reduce the blackout, it is necessary to back up the source voltage to supply the load. Back up voltage source is installed parallel work interchangeably automatically before getting into the load-called System Spot Network. System parallel two voltage sources a medium voltage cubicles called Automatic Change Over. To determine the reliability of before and after you install ACO then assigned a reliability index that is SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index). Once installed, ACO never experienced a blackout, so that the value of the index calculation SAIFI realization in the previous field is 0.05 outages / year to zero. Similarly, the calculation of SAIDI realization in the previous field is 0.112 hours / year to Zero